MODEL PENGENDALIAN MATERIAL PADA INDUSTRI BETON READY MIX - Toyfur, Mona Foralisa (CANTILEVER, 2007)
Ready mix concrete is chosen which project need large amount of concrete. For ready mix concrete producer, must have controlling system to give best quality. The system has to control how much material has to be stored because it will influence ordering cost, carrying cost, shortage cost, set up cost. This study develop a model that analyze when the producer ordering materials and how much material they order. This model can be used to define optimum order, safety stock, reorder point, cycle time of order and optimum safety capacity.